Digest: Adaptation and isolation: Testing genetic and environmental barriers to hybridization in Silene*. (2nd January 2019) - Richards, Thomas J.
Abstract: Species differences are maintained by the cumulative effect of factors that reduce gene flow between divergent lineages. In this issue, Karrenberg et al. quantify multiple genetic and environmental barriers to gene exchange between two closely related plant species and find that adaptation to divergent environments has the greatest effect on reproductive isolation.